Big data science issues in distributed database - Kasim, Shahreen; Azemi, Liesa; Anuar, Lidiya; Anuar, Aliah; Zainal, Kamilia; Basri, Ashikin; Omar, Nurul Aswa (Penerbit UTM Press, 2018)
This paper reviewed on the issues that occurs by Big Data Science such as challenges, opportunities, good practices and tools required to run Big Data Science. The paper refers to different techniques used to define the requirements on data management, access control and security. The paper also explains on how Big Data helps in contributing its function towards the development of distributed database.